Substance Use Among Lawyers and Law Students: A Scoping Review - Aidam, Kizito; Adawudu, Emefa A. (European Journal of Mental Health, 2024)
Introduction: Lawyers are uniquely vulnerable to substance use and disorders due to the use of different substances mainly because of the demanding and adversarial nature of the legal profession. Substance use often begins during law school years.Aims: This study aims to examine substance use and disorders due to the use of different substances.Methods: A scoping review was adopted to collect literature from January 2000 to November 2023. The review followed the Arksey and O’Malley framework. Literature was retrieved from CINAHL Complete, PubMed, PsycINFO, Web of Science, and Scopus. A total of 1,808 studies were retrieved and 14 were included for the final synthesis. The combined sample size was 16,722, comprising 15,150 lawyers and 1,572 law students. Data was extracted into a data matrix and then synthesized into the results.Results: Many lawyers and law students have experienced substance use disorders or problematic use. Alcohol and tobacco were the most used substances among them. Suicide due to substance use was also detected. Findings reveal the use of illicit substances, demographic disparities in substance use, and unprofessional behavior such as substance use during working hours. The role of support systems in battling substance use was critical among lawyers and law students. Even though few lawyers sought help for substance use related issues, treatment was effective.Conclusions: Substance use is pervasive in the legal profession. Although various health promotion and education interventions have been carried out to address this problem, the scale of the problems